About the need for diversity in labour law - Gładoch, Monika (Acta Universitatis Lodziensis. Folia Iuridica, 2019)
There is a conviction that if labour law is to protect the employee it in its essence requires restrictions. Therefore, the principle of contract freedom should be limited. Otherwise, there will be violation of the labour law system. Otherwise, there will be violation of the labour law system. It is only a step away from the statement that freedom in labour law may pose a threat to the implementation of the basic function in labour law. In other words, the greater uniformity i.e. uniformity of institutions, the greater the certainty and effectiveness of the protective function of labour law. Meanwhile, the employee protection function cannot be a barrier to the development of labour law. The labour law of the 21st century requires diversity. Only thanks to new forms of employment, work organization and flexibility, labour law can meet challenges of the labour market.